Dissociative Identity Disorder Scan in National Wrestlers and Comparison According to Several Variables - Ünsal Tazegül (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
Aims: The purpose of this study was to scan dissociative identity disorders in wrestlers who represented their nations in International tournaments. Material and methods: Dissociative Experiences Scale-DES was used as a data collection tool. Relational and Causative comparison models in quantitative research methods were also used in our research. Study group consisted of 14 male wrestlers competed in International tournaments. As sample number did not meet parametrical norms, non-parametric tests were taken place. Desctiptive statistics, Mann-Whitney U test, One-Way variance analysis and Spearmen Correlation analysis were used for statistical analysis. Results: As a result of statistical analysis, dissociative scores of wrestlers in study group were determined to be above 30. When this results was evaluated according to Dissociative Experiences Scale, it can be suggested that there might be dissociative disorders in wrestlers inside study group. Conclusions: Consequently, as a result of statistical analysis, Wrestlers were determined to have 30 and above dissociative scores. And when this is examined according to Dissociative Experience Scale; It indicated that there is a Dissociative disorder in wrestlers.